The Titanic treasure - Luper, Eric; Weber, Lisa K. (New York, NY : Scholastic Inc., 2017)
This time Cleo, Evan, the evil Mr. Locke, and his two trolls have all been transported to the Titanic--and if they do not find and save the priceless jeweled copy of the Rubiyat before the ship hits the iceberg and sinks they may all be lost at sea.
Appeals to 2nd-4th graders.
Reading level grade 3.
Keywords: Titanic (Steamship) -- Juvenile fiction; Books and reading -- Juvenile fiction; Libraries -- Juvenile fiction; Magic -- Juvenile fiction; Locks and keys -- Juvenile fiction; Adventure stories; Adventure fiction; Action and adventure fiction